Religious cultures in early modern India : new perspectives - O'Hanlon, Rosalind; Washbrook, D. A. (South Asian history and culture, 2011)
Contributed papers presented at a conference held at St. Antony's College, Oxford in June, 2009; first published in South Asian history and culture, Vol. 2, no. 2, Apr., 2011.